(untitled) (Texas Journal of Medical Science, 2022)
The pathogenesis factors of the individual tendency of adhesion process of each patient (53) have been investigated individually by the authors The results of research showed that 50 percent of patients have a tendency to adhesion process The indexes defining this process are blunt oppression of fibrinolys and the rising concentration of fibrinogen in the blood of operated sick children. In virtue of that the corresponding measures have been taken for an early prophylactic of the adhesion process.